Regulation of meristem and hormone function revealed through analysis of directly-regulated SHOOT MERISTEMLESS target genes - Tamara Lechon; Nicholas A. Kent; James A. H. Murray; Simon Scofield (Scientific Reports)
Abstract The Arabidopsis Knotted1-like homeobox (KNOX) gene SHOOT MERISTEMLESS (STM) encodes a homeodomain transcription factor that operates as a central component of the gene regulatory network (GRN) controlling shoot apical meristem formation and maintenance. It regulates the expression of target genes that include transcriptional regulators associated with meristem function, particularly those involved in pluripotency and cellular differentiation, as well as genes involved in hormone metabolism and signaling. Previous studies have identified KNOX-regulated genes and their associated cis-regulatory elements in several plant species. However, little is known about STM-DNA interactions in the regulatory regions of target genes in Arabidopsis. Here, we identify and map STM binding sites in the Arabidopsis genome using global ChIP-seq analysis to reveal potential directly-regulated STM target genes. We show that in the majority of target loci, STM binds within 1 kb upstream of the TSS, with other loci showing STM binding at more distal enhancer sites, and we reveal enrichment of DNA motifs containing a TGAC and/or TGAT core in STM-bound target gene cis-regulatory elements. We further demonstrate that many STM-bound genes are transcriptionally responsive to altered levels of STM activity, and show that among these, transcriptional regulators with key roles in meristem and hormone function are highly represented. Finally, we use a subset of these target genes to perform Bayesian network analysis to infer gene regulatory associations and to construct a refined GRN for STM-mediated control of meristem function.